PENGARUH LIKUIDITAS, LEVERAGE, DEBT DEFAULT, FIRM GROWTH DAN DISCLOSURE TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2008-2013 - RAFFLESIA, YANDIE (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACT   The aim of this study was to analyze the influence of liquidity, leverage, debt default, firm growth, and disclosure on acceptance of going concern opinion audit. The population used in this study is a company listed on the Indonesian stock exchange in the period 2008-2013 with a sample of company property and real estate. This study uses secondary data from financial statements that have been audited from Indonesia stock exchange website. Tests conducted by five independent variables that is liquidity, leverage, debt default, firm growth, and disclosure. With the dependent variable, namely going concern audit opinion, the tests performed with the IBM SPSS program by means of logistic regression. The results showed that the status of debt default and disclosure significantly influence the going-concern audit opinion while the other independent variables, namely liquidity, leverage, and firm growth does not affect the going concern audit opinion in this study.   Keywords: liquidity, leverage, debt default, firm growth, disclosure, and going concern opinion